An unusual case of tubercular liver abscess presenting as pericardial effusion - K. B., Vismaya; Rashid, Rihan (International Surgery Journal, 2023)
Tropical nations like India frequently have liver abscess. They are typically amoebic or pyogenic abscesses. It can sporadically be a sign of hepatic tuberculosis (TB). Hepatic tuberculosis should be suspected in cases where the patient doesn’t present with typical complaints of pyogenic/amoebic abscess without response to commonly used antibiotics. Pyogenic/amoebic liver abscesses show the rare complication of rupture into the pericardium, especially if the abscess is left sided. However, a tubercular pericardial effusion presenting with rupture into the pericardium has rarely been reported. We present to you a case of tubercular pericardial effusion in a known diabetic patient secondary to ruptured liver abscess presenting to the emergency department with chief complaints of breathlessness, chest pain and bilateral pedal edema.